Oxford international lower secondary english workbook 6 - Barber,Alison; Mark Saunders (Karachi: Oxford University Press, 2023)
The Oxford International Lower Secondary English Workbook 6 provides focused practice that complements the Student Book, helping students strengthen essential language skills. It includes a wide range of tasks in comprehension, grammar, vocabulary, and writing, with clear instructions and progressive exercises. The workbook encourages students to think critically, respond creatively, and apply language in different contexts. Through engaging passages and activities, it supports learners in developing accuracy, fluency, and confidence in both written and spoken English. It is structured to promote independent learning while reinforcing classroom teaching, making it a valuable resource for revision, homework, and skill-building.
The Oxford International Lower Secondary English Workbook 6 is designed to provide structured practice and reinforcement of the skills taught in the corresponding Student Book. It supports learners in developing reading comprehension, writing, grammar, vocabulary, and critical thinking. Each activity is carefully graded to match the age and level of students, ensuring a balance between challenge and accessibility. The workbook encourages independent learning by providing exercises that help students consolidate classroom lessons, while also promoting creativity through tasks such as guided writing, comprehension questions, and vocabulary enrichment. With a global perspective and engaging texts, it not only builds strong language skills but also fosters confidence in communication. The workbook is ideal for classroom use, homework assignments, and self-study, making it an essential companion for both teachers and learners in developing a solid foundation in English.
Keywords: Reading comprehension; Literary texts and non-fiction